Evaluation of Visceral Artery Displacement by Endograft Delivery System Insertion. (April 2014) - Maurel, Blandine; Hertault, Adrien; Gonzalez, Teresa Martin; Sobocinski, Jonathan; Roux, Marielle Le; Delaplace, Jessica; Azzaoui, Richard; Midulla, Marco; Haulon, Stéphan
Purpose: To assess the displacement of the aorta and its visceral branch ostia after insertion of a rigid system including a stiff guidewire and endograft delivery system during endovascular aneurysm repair (EVAR). Methods: Between January and May 2013, 20 consecutive patients (19 men; mean age 67.2 years, range 61–83) undergoing EVAR (n=13) or fenestrated EVAR (FEVAR, n=7) were prospectively enrolled. Each patient underwent an intraoperative contrast-enhanced cone beam computed tomography (ceCBCT) acquisition after the insertion of the endograft delivery system. Each ceCBCT was loaded on a workstation and manually registered with the preoperative computed tomographic angiogram (CTA) in a way that optimized superposition of the spine from both images. The locations of the superior mesenteric artery (SMA) and of both renal artery ostia were depicted in 3D multiplanar reconstructions by 3 independent operators on the CTA and on the ceCBCT. Motion of the aortic segment at the level of the visceral arteries was estimated by the barycenter of the origin of the SMA and both renal arteries. Results: The ostium displacement between the CTA and ceCBCT images was 6.7 mm (range 2.2–13.5) for the SMA; 6.2 mm (2.5–13.5) and 6.4 mm (1.9–14.5) for the right and the left renal arteries, respectively; and 5.5 mm (2.3–11.4) for the aortic segment. The displacement was mostly posterosuperior and to the left (65%). The radiation dose and contrast volume required to perform the ceCBCT were 30% and 41%, respectively, of the amounts used in the EVAR procedures. Conclusion: This study demonstrates a significant displacement of the main aortic branches after rigid material insertion. Image fusion applications aimed at providing intraoperative guidance must allow an easy and rapid repositioning of the overlay during the procedure to match the deformation of the aortic anatomy during the procedure.